(untitled) (Security Dialogues, 2025)
In the period from 9 until 11 July, 2024, the 75 anniversary Summit of the Heads of State and Government of the Alliance was held in Washington, in the conditions of a conventional threat to the security of the Alliance and in a time of war on the soil of Europe. NATO leaders discussed strategically important issues related to deterrence and defense, long-term support for Ukraine and cooperation with the Alliance’s global partners. The focus in strengthening the Alliance’s defense and deterrence is placed through “investing in new, modern high-end military capabilities” and “increasing the readiness of our forces,” (Stoltenberg, 2024) all underpinned by major increases in defence spending across the Alliance by supporting the increase in defense spending. I have suggested that at the Summit, we agree a big NATO role in coordinating and providing security assistance and training for Ukraine,” he said. “I strongly believe that we need a firmer, stronger institutionalized structure for the support. Ad-hoc, short term, voluntary announcements are good – but in the long term, we need more predictable, stronger support for Ukraine. In relation to the support of Ukraine, NATO is expected to increase its role in the coordinating and providing security assistance and training for Ukraine. According to Stoltenberg, this implies the establishment of a “firmer, stronger institutionalized structure” that will ensure a more predictable and sustainable long-term support of Ukraine. Cooperation with partners is crucial for security and stability because security is not only a regional issue but also a global issue.